Comparison of transperineal and transrectal targeted prostate biopsy using Mahalanobis distance matching within propensity score caliper method: A multicenter study of Turkish Urooncology Association - (:unkn) unknown (My University, 2021)
OBJECTIVE: To compare the clinically significant prostate cancer (csPC)-detecting results of transperineal and transrectal targeted biopsy (TPTB and TRTB, respectively) by performing matching analysis. PATIENTS AND METHODS: This study has used the PC and prostate biopsy database from the Turkish Urooncology Association. A total of 1143 patients with Prostate Imaging-Reporting and Data System (PI-RADS) with ≥3 lesions on multiparametric magnetic resonance imaging (mpMRI) and who had received a software-guided transperineal/transrectal MRI/transrectal ultrasound (TRUS) fusion prostate biopsy with concomitant standard systematic 12-core biopsy were included in this study. csPC detection rates of the TP and TR approaches were compared following Mahalanobis distance matching within propensity score caliper method. The following four variables were selected as covariates for the matching procedure: age, digital rectal examination findings, PSA density, and the index lesion PI-RADS score. RESULTS: The matched sample included 508 TR and 276 TP patients. In both the TP and the TR groups, targeted biopsy was superior to systematic biopsy in detecting csPC (27.5% vs. 24.6%, p < 0.001 and 19.5% vs. 16.3%, p < 0.0001, respectively). Both TPTB and TP systematic biopsy was found to be superior to TRTB and TR systematic biopsy in terms of csPC detection (27.5% vs. 19.5%, p = 0.012 and 24.6% vs. 16.3%, p = 0.006). In patients with an anterior index lesion, an apical index lesion, and a larger prostate, the superiority of TPTB to TRTB was found to be more prominent in terms of csPC detection (37.8% vs. 18.3%, p = 0.044; 34.6% vs. 14.7%, p = 0.002; and 25% vs. 5.1%, p = 0.033, respectively). CONCLUSION: Targeted biopsy was found to be superior to systematic biopsy in detecting csPC in both the TP and the TR approaches. The TP approach is preferred because of its clear superiority in detecting csPC in targeted biopsy, especially in patients with anterior and apical lesions and with larger prostates.
Keywords: prostate cancer; fusion biopsy; targeted biopsy; transperineal; transrectal